2020
DOI: 10.1177/2373379920962410
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Allyship Through Anti-Oppression Workshops for Public Health Students: A Mixed Methods Pilot Evaluation

Abstract: This pilot mixed methods evaluation describes the impact of an antioppression workshop on allyship development among a group of public health graduate students. After completing a mandatory antioppression workshop, a survey including closed- and open-ended questions was administered to 41 public health students specializing in health promotion. Closed-ended questions gathered basic demographic data and Likert-type scale responses to assess changes in participant knowledge, awareness, and attitudes surrounding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Our special issue of December 2021 on the pedagogy of antiracism offered articles covering such topics as student voices in the struggle against racism, promising practices for addressing racism in the classroom, and engaging with communities to promote social justice. As a sample of these thought-provoking and instructive papers, I encourage readers to explore Djulus et al (2021) and Aqil et al (2021), who discuss approaches that help advance anti-oppression oriented pedagogy. Several papers in this issue address ways in which academics can transcend institutional reinforcement of social biases and constraints and foster equity-focused education and professional development (Carlos & Pallai, 2021; Perez et al, 2021).…”
Section: Framing Our Pedagogymentioning
confidence: 99%
“…Our special issue of December 2021 on the pedagogy of antiracism offered articles covering such topics as student voices in the struggle against racism, promising practices for addressing racism in the classroom, and engaging with communities to promote social justice. As a sample of these thought-provoking and instructive papers, I encourage readers to explore Djulus et al (2021) and Aqil et al (2021), who discuss approaches that help advance anti-oppression oriented pedagogy. Several papers in this issue address ways in which academics can transcend institutional reinforcement of social biases and constraints and foster equity-focused education and professional development (Carlos & Pallai, 2021; Perez et al, 2021).…”
Section: Framing Our Pedagogymentioning
confidence: 99%
“…13 Research has shown a profound need for ongoing anti-oppression and allyship training among future public health and global health students and professionals. 14 This need is urgent in the context of COVID-19, decolonisation efforts and Black Lives Matter.…”
Section: Include Anti-racism Equity and Diversity As Core Contentmentioning
confidence: 99%
“…Learning about oppression that includes racism—specifically how certain groups are disadvantaged and disproportionately impacted by the public health system, and how professors, as embedded in the system, can unconsciously and sometimes consciously misuse our power and privilege when working with vulnerable communities—is therefore key to disrupting the marginalisation of these groups and to integrate anti-oppression and anti-racism into practice in global health. 14 Indeed, every global health educator must actively contemplate and address their complicity in the very systems of inequality that cause health disparities. This includes but is not limited to understanding one’s implicit (and explicit) biases.…”
Section: Include Anti-racism Equity and Diversity As Core Contentmentioning
confidence: 99%
“…Pedagogy in Health Promotion provides examples of the rich variety and scope of the scholarship of teaching and learning. SoTL work observes and comments on teaching practice (Flores et al, 2021;Kratzke et al, 2021), develops and tests theories and evidence-based frameworks (Kuganathan et al, 2021;Miller et al, 2021), provides quantifiable explanations (Blavos et al, 2020;Foutch et al, 2020), pursues qualitative explorations (Muzaffar et al, 2020), engages in experimental research (Djulus et al, 2020), increases our ability to be compassionate and inclusive (James et al, 2020;Mezuk et al, 2021) and shares deep reflections about our collective experience of teaching and learning (Derreth et al, 2021). Combined, these scholarly endeavors help us to better understand how to provide effective and supportive education to health promotion and public health students, develop and challenge critical skills for health promotion and public health practice and ultimately, benefit communities and populations, and improve health outcomes.…”
mentioning
confidence: 99%